Digital Copyright Asset as an Investment and Paradox of Publicity - Victor S. VORONOV; Alexander V. KAZANSKY; Neli R. ABRAMISHVILI (Communications of International Proceedings, 2020)
The purpose of this work is to establish whether the placement by the author of his own digital copyright assets (DCA) in the microstock portfolio can be considered as an investment. The second goal is related to the fact that the leading intermediary companies of this type entered the stock market, and their publicity made possible fundamentally different ways of implementing investments. Therefore, part of the work is devoted to the analysis of problems and paradoxes of publicity. The research methodology is based on comparative analysis using the so-called Howey test. As a result of the analysis, it was found that DCA meet the criteria for belonging to investment activities, and can be considered as a new promising investment resource.
Keywords: Digital Copyright Asset; Howey Test; Investment; Public Company; Risk.